2017
DOI: 10.1002/biot.201700484
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Engineering of Post‐PKS Modification Bottlenecks for Ansamitocin P‐3 Titer Improvement in Actinosynnema pretiosum subsp. pretiosum ATCC 31280

Abstract: The type-I polyketide ansamitocin P-3 (AP-3) is a potent antitumor agent. Its production is most likely hampered by the required multiple substrate supplies and complicated post-PKS modifications in Actinosynnema pretiosum subsp. pretiosum ATCC 31280. For titer improvement, gene ansa30, encoding for a glycosyltransferase competing for the N-demethyl-AP-3 (PND-3) intermediate for AP-3 biosynthesis, was initially inactivated. In the mutant NXJ-22, the AP-3 titer was increased by 66% along with an obvious accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…There were 37 genes in the model predicted as influential genes, and 21 of them were found to be essential, whose deletions causing a decrease of AP-3 production more than 90% ( Table S3 in Supplementary Materials ). The enriched pathways [ 40 ] for influential genes is shown in Figure 3 , and the genes in AP-3 biosynthesis pathway has the most significant effect on AP-3 production, which is consistent with previous finding [ 23 ]. In addition, central carbohydrate metabolism, histidine metabolism, and branched-chain amino acid pathway are also enriched with the influential genes, providing precursors for AP-3 biosynthesis, such as malonyl-CoA (coenzyme A), methylmalonyl-CoA, methoxymalonyl-ACP (acyl carrier protein), glutamate, and valine.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…There were 37 genes in the model predicted as influential genes, and 21 of them were found to be essential, whose deletions causing a decrease of AP-3 production more than 90% ( Table S3 in Supplementary Materials ). The enriched pathways [ 40 ] for influential genes is shown in Figure 3 , and the genes in AP-3 biosynthesis pathway has the most significant effect on AP-3 production, which is consistent with previous finding [ 23 ]. In addition, central carbohydrate metabolism, histidine metabolism, and branched-chain amino acid pathway are also enriched with the influential genes, providing precursors for AP-3 biosynthesis, such as malonyl-CoA (coenzyme A), methylmalonyl-CoA, methoxymalonyl-ACP (acyl carrier protein), glutamate, and valine.…”
Section: Resultssupporting
confidence: 89%
“…In this study, we reconstructed and validated the first GSMM of A. pretiosum ATCC 31280 based on the newly sequenced genome (Genebank accession number: CP029607). Then we integrated the model with time-course transcriptome data of a high-yield mutant strain NXJ-24 [ 23 ] to investigate the change of metabolic flux distribution during the fermentation process. Furthermore, potential strategies for improving AP-3 production were predicted by in silico strain design based on the established model.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirmed that overexpression of asmUdpg could pull more carbon flux from primary metabolism to UDP‐glucose pool and AHBA biosynthesis pathway in O asm13‐17 . As a result, the AP‐3 production titer reached 680.5 mg/L in O asm13‐17 : asmUdpg , which is much higher than previous reports, including those by random mutagenesis (Chung & Byng, ; Kuo, Byng, & Widdison, ), medium optimization (Fan et al, ; Gao et al, ; Jia & Zhong, ; Li et al, ; Lin et al, ), modification of regulator genes (Bandi et al, ; Ng, Chin, & Wong, ; Pan, Kang, Wang, Bai, & Deng, ), and pathway engineering (Du et al, ; Fan, Hu, Wei, Bai, & Hua, ; Fan, Zhao et al, ; Ning, Wang, Wu, Kang, & Bai, ; M. Zhao et al, ). As summarized in Table , the recent record of AP‐3 titer in M‐ asmUdpg:asm13‐17 , which coexpressed asm13‐17 and asmUdpg in a high‐producing mutant M (Du et al, ), was lower than O asm13‐17 : asmUdpg here.…”
Section: Discussionmentioning
confidence: 66%
“…First, when enhanced green fluorescent protein and CspL were simultaneously expressed in E. coli at 45 °C, the co-expression of both recombinant proteins significantly increased growth (reduced lag phase) without causing any deleterious effects on green fluorescent protein expression or function (Figure 7A). Second, the expression of CspL in Actinosynnema pretiosum ATCC31280 (Ning et al, 2017) significantly improved the production of the potent antitumor agent ansamitocin P-3 (a 1.6-fold increase) (Figure 7B). Third, the expression of CspL in high-temperature (50 °C) cultures of a recently engineered Bacillus licheniformis ATCC14580 strain (BN11) (Li et al, 2016) significantly increased both D-lactate production (1.4-fold increase) and glucose consumption (1.33-fold increase) (Figure 7C).…”
Section: Resultsmentioning
confidence: 99%